2022
DOI: 10.52973/rcfcv-e32091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Blood Gases and Hemogram Parameters in the Diagnosis of non Neurogenic Distemper and Parvoviral Enteritis in Dogs with Acute Gastroenteritis

Abstract: Canine parvovirus (CPV) and canine distemper virus (CDV), which are seen mostly in dogs younger than 6 months (mos) old with high mortality despite early diagnosis and treatment, cause various hematological abnormalities and clinical symptoms accompanied by gastroenteritis findings. Since the methods developed for definitive ante-mortem diagnosis are time-consuming and require expertise and equipment, routine laboratory tests such as blood gases and hemogram analyzes still maintain their importance in the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Furthermore, low Hb levels may result from reduced erythropoiesis due to direct damage by CPV to the bone marrow, and accumulation of toxic waste products during the viremia and febrile phase as well as the dog's previous poor health (18,20). Besides, the changes in these parameters may be associated with hypochromic anemia caused by proinflammatory cytokines and the disruption of the development of reticulocytes by converting iron into a less usable form (16). In the present study, the WBC, granulocyte, MCH, MCHC and Hb values of the CPE Group were lower (p<0.031) and the RDW value was higher (p<0.001) when compared to the Control Group.…”
Section: Discussionsupporting
confidence: 39%
See 4 more Smart Citations
“…Furthermore, low Hb levels may result from reduced erythropoiesis due to direct damage by CPV to the bone marrow, and accumulation of toxic waste products during the viremia and febrile phase as well as the dog's previous poor health (18,20). Besides, the changes in these parameters may be associated with hypochromic anemia caused by proinflammatory cytokines and the disruption of the development of reticulocytes by converting iron into a less usable form (16). In the present study, the WBC, granulocyte, MCH, MCHC and Hb values of the CPE Group were lower (p<0.031) and the RDW value was higher (p<0.001) when compared to the Control Group.…”
Section: Discussionsupporting
confidence: 39%
“…In addition, in dogs younger than 3 week-old, the virus can also affect the myocardium (15). In addition, it has been reported that dogs less than 6 monthold, unvaccinated or given an inadequate/wrong vaccination program are susceptible to CPE (2,3,16). In the present study, the rate of sepsis development in dogs with CPE was determined as 46.29%.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations